Writing: A Mode of Thinking - Fu, Danling; Hansen, Jane (Language arts, 2012)
[...]while we talk about high-order thinking or critical thinking in our teacher programs or in inservice workshops, teacher workshops, or even our curriculum standards, we don't actually see the depth of thinking demonstrated in our teaching or in our students' work. [...]we need to teach writing in every subject, not just in language arts. Because writing deepens reading comprehension, subject knowledge learning- math, science, social studies, language development.